Influence of conditional cash transfer program on prenatal care and nutrition during pregnancy: NISAMI cohort study - Santana, Jerusa da Mota; Pereira, Marcos; Lisboa, Cinthia Soares; Santos, Djanilson Barbosa; Oliveira, Ana Marlucia (São Paulo Medical Journal, 2022)
BACKGROUND: There are few studies on the influence of a cash transfer program on nutritional outcomes from pregnancy. OBJECTIVES: To analyze how a Brazilian conditional cash transfer program (Bolsa Familia Program, BFP) was associated with changes in body mass index (BMI) and food consumption among pregnant women. DESIGN AND SETTING: Cohort study on 250 pregnant women (≥ 18 years of age) in Brazilian prenatal services. METHODS: A food frequency questionnaire was used to evaluate dietary intake. Weight was measured in each gestational trimester. Generalized estimation equations and structural equation modeling were used for statistical analyses. Correlations were analyzed using standardized coefficients (SCs). RESULTS: Women benefitting from the BFP were of greater age and had lower education. The BFP exerted a direct negative effect on the pregnant women’s consumption choices regarding refined grains, regional foods, vegetable oil, sausages, salted meats and snacks (SC = -0.10) and on maternal BMI (SC = -0.12). Among the intermediate variables, we observed that the time elapsed since pregnancy and the month of prenatal onset had direct negative effects; and that the number of visits to doctors, family income and number of years of education had direct positive effects. CONCLUSIONS: Beneficiaries were less likely to increase their BMI outside of the recommended standards and had a greater tendency to receive prenatal care. Participation in the BFP had a direct negative effect on adherence to unhealthy diets.